2016
DOI: 10.1007/s10571-016-0355-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1: Role Under the Condition of Ischemia/Hypoxia

Abstract: Silent information regulator factor 2-related enzyme 1 (sirtuin 1, Sirt1) is a nicotinamide adenine dinucleotide-dependent deacetylase, which can deacetylate histone and non-histone proteins and other transcription factors, and is involved in the regulation of many physiological functions, including cell senescence, gene transcription, energy balance, and oxidative stress. Ischemia/hypoxia injury remains an unresolved and complicated situation in the diseases of ischemia stroke, heart failure, and coronary hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(103 citation statements)
references
References 93 publications
1
96
0
6
Order By: Relevance
“…Interestingly, in the present study, we demonstrated that Sirt1 could also regulate miRNA expression. Recently, accumulating evidence has strongly implied that SIRT1, a highly conserved NAD‐dependent deacetylase that promotes cell survival under oxidative stress could deacetylate various transcription factors including NF‐κB, which in turn regulate downstream cellular pathways associated with oxidative stress . Therefore, activation of SIRT1‐mediated NF‐κB deacetylation to suppress oxidative stress and inflammation represents a potentially treatment strategy for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the present study, we demonstrated that Sirt1 could also regulate miRNA expression. Recently, accumulating evidence has strongly implied that SIRT1, a highly conserved NAD‐dependent deacetylase that promotes cell survival under oxidative stress could deacetylate various transcription factors including NF‐κB, which in turn regulate downstream cellular pathways associated with oxidative stress . Therefore, activation of SIRT1‐mediated NF‐κB deacetylation to suppress oxidative stress and inflammation represents a potentially treatment strategy for RA.…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1 deficiency or knockdown attenuated the neuroprotection of NAD + in ischemic stroke 13, 42 . Sirt1 mediated deacetylation of p53, reducing its pro-apoptotic effects; and it also deacetylated NF-κB, reducing its pro-inflammatory effects 43 . p53 mediates apoptosis through several pathways and results in activation of caspase-3, the executor of cell death 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Sirt1 is another deacetylase that modulates transcriptional activation in ischaemia/hypoxia (Meng et al . ).…”
Section: Hypoxia‐responsive Transcriptional Regulationmentioning
confidence: 97%